Snakes and ladders media can help prevent risky sexual behaviour in teenagers - Putii, Mezy Aullia; Yorita, Epti; Yuniarti, Yuniarti; Efriani, Rolita; Burhan, Rialike (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: In Indonesia, on average, adolescent boys and girls have their first sexual experience when they are 15 and 19 years old, which triggers risky sexual behaviors resulting in sexually transmitted diseases (STDs), HIV/AIDS, unwanted pregnancies, abortions, and even death. Therefore, educational media is needed to increase positive behavior in adolescents. Objectives: This study aims to determine the influence of snake and ladder game media on adolescent sexual behavior. Methods:The research design was a quasi-experimental pretest and posttest group with a control group. The treatment group is teenagers who are given education with snake and ladder game media while the control group is teenagers who are given education through monopoly games. A total of 100 samples were selected using the prolpoltiolnatel stratifield random sampling technique. The data were analyzed by wilcoxon and mann whitney tests. Results: As a result, there was an influence of education with snake and ladder game media on the average knowledge score of p=0.000), attitude p=0.000), behavior p=0.000). The results of the statistical test also showed that there was an influence of monopoly game media on the average knowledge score p=0.00, attitude=0.00, behavior p=0.00. The snake and ladder game media is more effective in increasing knowledge p=0.00, attitude p=0.002 compared to monopoly game media. Conclusions: the snakes and ladders game media is more effective in increasing adolescents' knowledge about risky sexual behaviour than the monopoly game media. Health care providers must take advantage of snake and ladder educational media to increase knowledge, attitudes and prevent risky sexual behavior.